The Portrayal of American Academic Culture in The Bad Teacher Movie: The Portrayal of American Academic Culture - Junaid, Syahruni; Asnur, Sardian Maharani; Rauf, Masykur; Aisyah; Sulastri, Sri (Journal of Islamic Culture and Literature (JICeL), 2023)
This research discusses education that is responsive to culture, which means an embodiment of respect for the identity of all students as individual students. The purpose of this study is to reveal the depiction of academic culture owned by the United States through the film The Bad Teacher. The theory used in this study is that education that is responsive to culture will provide instructions to teachers to implement an education and learning system that connects students with social life, desires, and depictions of the environment outside of academia (Ambarwati et al., 2020). Then it was analyzed using a descriptive qualitative research design method by applying conversational analysis in the film The Bad Teacher. Researchers used note-taking as an instrument to find out more valid data for this study obtained by watching and listening to conversations in films that show academic culture in the United States. The results showed that there were 6 depictions of academic culture and 1 depiction of toxic academics. The researcher concludes that the method used in this study is a descriptive qualitative research design by applying conversational analysis in the film The Bad Teacher.Keywords: Portrayal, Academic Culture, The Bad Teacher Movie